Determinant of Pulmonary Tuberculosis in Outpatients at Daya Hospital, Makassar City - Handayani, Sri; Musfirah, Musfirah; Apriana, Apriana (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Indonesia ranks third with the highest number of TB patients in the world after India and China. Initial data collection conducted at Daya Kota Makassar Regional General Hospital revealed that Pulmonary Tuberculosis is among the top 10 diseases in both outpatient and inpatient cases. The incidence of Pulmonary TB in outpatient cases was 783 in 2019, 210 in 2020, and 238 in 2021. The objective of this research is to determine the determinants of pulmonary tuberculosis incidence in outpatient patients at Daya Kota Makassar Regional General Hospital. The research method employed is quantitative research with a cross-sectional design. The population for the study includes all outpatient patients in the Pulmonary Clinic of Daya Kota Makassar Regional General Hospital, totaling 142 individuals, with a subject of 49 subjekts selected using purposive sampling technique. Bivariate analysis uses Chi-square, and multivariate analysis employs logistic regression. The research results indicate a correlation between knowledge (p-value=0,004), smoking behavior (p-value=0,003), and nutritional status (p-value=0,019) with the incidence of Pulmonary Tuberculosis. However, there is no socio-economic relationship with Pulmonary Tuberculosis incidence (p-value=0,169) at Daya Kota Makassar Regional General Hospital. It is recommended that the community participate in the socialization activities for preventing the risk of Pulmonary Tuberculosis provided by health cadres to reduce the incidence of Pulmonary Tuberculosis.